A Retrospective Cohort Study on Mortality and Neurodevelopmental Outcomes of Preterm Very Low Birth Weight Infants Born to Mothers with Hypertensive Disorders of Pregnancy - Kono, Yumi; Yonemoto, Naohiro; Nakanishi, Hidehiko; Hosono, Shigeharu; Hirano, Shinya; Kusuda, Satoshi; Fujimura, Masanori; for the Neonatal Research Network Japan (American Journal of Perinatology, 2021)
Objective We examined the effects of maternal hypertensive disorders of pregnancy (HDP) on the mortality and neurodevelopmental outcomes in preterm very low birth weight (VLBW) infants (BW ≤1,500 g) based on their intrauterine growth status and gestational age (GA).Study Design We included singleton VLBW infants born at <32 weeks' gestation registered in the Neonatal Research Network Japan database. The composite outcomes including death, cerebral palsy (CP), and developmental delay (DD) at 3 years of age were retrospectively compared among three groups: appropriate for GA (AGA) infants of mothers with and without HDP (H-AGA and N-AGA) and small for GA (SGA) infants of mothers with HDP (H-SGA). The adjusted odds ratios (AOR) and 95% confidence intervals (CI) stratified by the groups of every two gestational weeks were calculated after adjusting for the center, year of birth, sex, maternal age, maternal diabetes, antenatal steroid use, clinical chorioamnionitis, premature rupture of membranes, non-life-threatening congenital anomalies, and GA.Results Of 19,323 eligible infants, outcomes were evaluated in 10,192 infants: 683 were H-AGA, 1,719 were H-SGA, and 7,790 were N-AGA. Between H-AGA and N-AGA, no significant difference was observed in the risk for death, CP, or DD in any GA groups. H-AGA had a lower risk for death, CP, or DD than H-SGA in the 24 to 25 weeks group (AOR: 0.434, 95% CI: 0.202–0.930). The odds for death, CP, or DD of H-SGA against N-AGA were found to be higher in the 24 to 25 weeks (AOR: 2.558, 95% CI: 1.558–3.272) and 26 to 27 weeks (AOR: 1.898, 95% CI: 1.427–2.526) groups, but lower in the 30 to 31 weeks group (AOR: 0.518, 95% CI: 0.335–0.800).Conclusion There was a lack of follow-up data; however, the outcomes of liveborn preterm VLBW infants of mothers with HDP depended on their intrauterine growth status and GA at birth.Key Points
Keywords: hypertensive disorders of pregnancy; preterm; small for gestational age; appropriate for gestational age; mortality; cerebral palsy; development